Literature review: culture and the use of food additives (Research, Society and Development, 2021)
Cuniculture is the branch of animal husbandry that deals with the productive, economic and rational breeding of rabbits. From the Second World War onwards, there was a need to produce, more quickly and efficiently, products of animal origin for human consumption. Thus, rabbits aroused interest because they are prolific, docile and fast reproductive animals. Raising rabbits can be considered an easy-to-implement activity, with simple management and installations, producing excellent quality meat for human consumption and its by-products that can be commercialized on a large scale and can be a great source of income for small and large producers. Food is the crucial point to achieve good production rates; as with other production systems, in rabbit farming, feeding represents 60 to 70% of the costs. Due to this, the use of additives seeks to increase feed efficiency, providing better productive and economic performance in animal production. Thus, nucleotides are additives composed of a nitrogenous base (purine or pyrimidine), a pentose and one or more phosphate groups. Within animal nutrition, dietary nucleotides have drawn attention for playing a role in the maintenance of intestinal health and may act as a solution to the use of antibiotics in the feeding of young animals. Therefore, it highlights the importance of studies and research to obtain new alternatives in feeding for production systems and keep data on rabbit production active.